Molecular Docking Assessment of Efficacy of Different Clinically Used Arsenic Chelator Drugs. (15th December 2013) - Majumder, Durjoy; Mukherjee, Sayan
Abstract : Arsenic contamination of ground water has become a global problem affecting specially, south-east Asian countries like Bangladesh and eastern parts of India. It also affects South America and some parts of the US. Different organs of the physiological system are affected due to contamination of inorganic arsenic in water. Animal studies with different chelators are not very conclusive as far as the multi/differential organ effect(s) of arsenic is concerned. Our docking study establishes the molecular rationale of blood test for early detection of arsenic toxicity; as arsenic has a high affinity to albumin, a plasma protein and actin, a structural protein of all cells including Red Blood Cells. This study also shows that there is a little possibility of male reproductive organs toxicity by different forms of inorganic arsenic; however, female reproductive system is very much susceptible to sodium-arsenite. Through comparative analysis regarding the chelating effectiveness among the available arsenic chelator drugs, meso-2, 3 dimercaptosuccinic acid (DMSA) and in some cases lipoic acid is the most preferred choice of drug for removing of arsenic deposits. This computational method actually reinforces the clinical finding regarding DMSA as the most preferred drug in removal of arsenic deposits from majority of the human tissues.